Associations of selenium status with all-cause and cause-specific mortality: a systematic review and meta-analysis of cohort studies - Cui, Zhixin; Xie, Ruijie; Lu, Xiaoting; Schomburg, Lutz; Brenner, Hermann; Schöttker, Ben (Redox Biology, 2025)
Objective - To provide a systematic review and meta-analysis of population-based cohort studies on the association of selenium status with all-cause and cause-specific mortality. - Methods - Relevant studies were identified through systematic searches of MEDLINE and ISI Web of Knowledge. Risk ratios (RRs) reported across categories of selenium biomarkers were recalculated as continuous RR estimations per standard deviation (SD) using generalized least squares for linear trend estimation and pooled in random effects meta-analyses. - Results - The literature search identified 20 studies, including 17 studies on all-cause mortality, 9 studies on cardiovascular mortality and 7 on cancer mortality. An increase of selenium biomarker concentration by one SD was associated with 13 % lower all-cause mortality (RR [95 %-confidence interval], 0.87 [0.83-0.90]), 11 % lower cardiovascular mortality (0.89 [0.84-0.94]) and 15 % lower cancer mortality (0.85 [0.78-0.94]). Although moderate heterogeneity was observed, the inverse association with all-cause mortality was robust across countries with low or adequate selenium supply, selenium measurement methods, recruitment years, study quality scores, follow-up lengths and sample sizes. The trim and fill method showed no indications of relevant publication bias. - Conclusion - Selenium biomarkers are inversely associated with all-cause, cardiovascular and cancer mortality in the general population and clinical trials among selenium deficient populations are still needed.
Online veröffentlicht: 10. Juli 2025, Artikelversion: 19. Juli 2025
Gesehen am 21.11.2025